Examining capacity for "cross-pollination" in a rural school district: A social network analysis case study. (September 2019) - Woodland, Rebecca H; Mazur, Rebecca
Teacher collaboration is a vital factor in successful school reform, and the networks in which educators are embedded support (or constrain) access to essential social capital resources. In this study, authors used social network analysis to examine the changing structure of teacher collaboration networks over the course of a rural District's 3-year Professional Learning Community (PLC) initiative. Visual depictions (sociograms) of district- and school-level teacher collaboration networks were generated, and measures of network cohesion – including size, density, connectedness, components, and degree – were calculated at three points in time. Authors worked in partnership with district administrators to explore how location of teachers and principals, and network capacity for diffusion of innovation, changed over time. School leaders may not know how to purposefully influence communication ties between teachers, relying instead on the invisible web of personal affiliations through which professional opinions travel. This study contributes to the field's understanding of how administrator choices about organizational structure affect "cross-pollination" and the networks through which teachers are able to access and contribute the knowledge and ideas they need in order to deliver high-quality curriculum and instruction to all students.